Mekro Bisnis Center IoT-Based Housing Security System with Automatic Barrier Using e-KTP Verification and Sound Indicators - Dzikri, Muhammad Aidil; Rahman, Maulia (Jurnal ICT : Information and Communication Technologies, 2025)
Residential security is an essential aspect of ensuring the comfort and safety of residents. However, the use of conventional systems such as manual security guards and barrier gates without identity verification is still commonly found, including at the Mekro Business Center Housing Complex. Problems arising from these systems include inefficiency, the potential for unauthorized access, and limitations in manual surveillance by security personnel. To address these issues, an automated system is needed to manage residential access in real-time and enhance overall security. This study aims to develop a security system based on the Internet of Things (IoT) using an automatic barrier gate equipped with e-KTP verification via RFID and a sound indicator for real-time notifications. The system was designed using the Fishbone Diagram approach as a reference in designing the components and workflow of the security system. The tools used include an ESP32 microcontroller, RFID RC522 module, infrared sensor, buzzer, and DFPlayer Mini speaker, all integrated with the Blynk application and a monitoring website. The testing process was conducted experimentally using the blackbox method through a miniature physical prototype simulation in six different scenarios. Out of 35 total tests, the system responded correctly 30 times under online conditions, achieving a 100% success rate in scenarios involving authorized access, unauthorized access, intrusion attempts, emergency access, and control via the application. All tests under offline conditions failed due to the lack of internet connectivity. The results show that this system can improve the efficiency and reliability of automatic access control in residential environments and support the performance of security personnel.